‘Candidatus Mycoplasma haemoalbiventris’, a novel hemoplasma species in white-eared opossums (Didelphis albiventris) from Brazil - Pontarolo, Giane Helenita; Kühl, Luís Felipe; Pedrassani, Daniela; Campos, Monique; Figueiredo, Fabiano Borges; Valente, Jessica Damiana Marinho; Gonçalves, Luiz Ricardo [UNESP]; André, Marcos Rogério [UNESP]; Vieira, Thállitha Samih Wischral Jayme; Vieira, Rafael Felipe da Costa; Roque de Barros Filho, Ivan (My University, 2020)
Opossums of the genus Didelphis are considered synanthropic animals due to their close contact with human beings. Previously, two species of hemotropic mycoplasmas (hemoplasmas) have been detected in opossums: ‘Candidatus Mycoplasma haemodidelphidis’ in the North American opossum (Didelphis virginiana) and a potentially novel hemotropic Mycoplasma sp. in the white-eared opossums (Didelphis albiventris) from Brazil. Accordingly, the aims of this study were as follows: (a) to determine the prevalence of hemotropic Mycoplasma spp. in free-ranging opossums, (b) to characterize molecularly the hemotropic Mycoplasma sp. infecting opossums and (c) to determine factors associated with hemoplasma infection in opossums from Canoinhas municipality, Santa Catarina State, southern Brazil. For this purpose, 50 white-eared opossums (33 captured and 17 road-killed animals) were evaluated by a pan-hemoplasma PCR assay based on 16S rRNA. Six out of 50 (12%; 95% CI: 5.6%–23.8%) opossums were infested by Ctenocephalides felis fleas. Twenty out of 50 (40%; 95% CI: 26.41%–54.82%) opossums tested positive for hemotropic Mycoplasma sp. by PCR. Sequencing and phylogenetic analysis of the 16S and 23S rRNA gene fragments confirmed that animals were infected by a potentially novel hemotropic Mycoplasma sp. previously reported in white-eared opossums from Brazil. No significant association was found between gender (p =.7759), trap area (p =.0887) or presence of fleas (p =.3811) and positivity for hemoplasmas. The potentially novel hemoplasma species seems to be highly prevalent in white-eared opossums from the states of Paraná, Santa Catarina and Mato Grosso do Sul. Based on the phylogenetic analyses of the 16S rRNA and 23S rRNA genes along with epidemiological data, the name ‘Candidatus Mycoplasma haemoalbiventris’ is proposed for this novel organism.
Keywords: Didelphis sp. hemotropic mycoplasmas; marsupials; ‘Candidatus Mycoplasma haemodidelphidis’